IMPLEMENTASI KURIKULUM PENDIDIKAN AGAMA ISLAM BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI DI SMPN 9 DEPOK - Ellya Verawati (Jurnal At-Tabayyun, 2020)
The implementation of information and communication technology curriculum at SMPN 9 Depok focuses on basic computer knowledge and operations, information processing for productivity, problem solving, exploration and communication. At each level, students are expected to be able to operate the computer properly. Barriers and support in the implementation of information and communication technology subjects. Obstacles that occur in the form of technical factors, namely the lack of facilities and infrastructure that support information and communication technology lessons, namely the inadequate number of computers available when compared to the number of students who use it. One computer must be used interchangeably by two students. Non-technical constraints are teachers who have not attended computer training in accordance with the current development of computer science. Then the use of English in the computer operational system. These obstacles are not an obstacle to progress for SMPN 9 Depok, the foundation continues to try to continuously improve the facilities that should be owned in the subjects of information and communication technology. How to overcome the obstacles that occur in the subjects of Information and Communication Technology is to build a larger laboratory space so that it can accommodate more computers and ultimately can maximize the means of computers, so it is expected that one computer can be used by one student. The use of English in computer operational systems, is overcome by trying to translate it in Indonesian, so it is expected that students understand about the operational system. Fourth, the teaching and learning process that is currently taking place at SMPN 9 Depok has not developed much creativity in using various learning models and methods, but to practice using computers teachers let students more actively interact and process information and communicate it. The teaching methods used are lecture and Q&A methods.